Economic policy uncertainty spillovers in Europe before and after the Eurozone crisis. (4th June 2021) - Tzika, Paraskevi; Fountas, Stilianos
Abstract: This paper focuses on economic policy uncertainty spillovers across Europe, before and after the outburst of the Eurozone crisis, using data for seven Eurozone countries for the period 2003–2019. At first, we analyze the spillovers of uncertainty in Europe via the estimation of the Diebold‐Yilmaz spillover index. The results indicate that uncertainty connectedness was 50.5% before the crisis, while it dropped to 30.6% afterwards indicating a sharp drop in uncertainty spillovers across the seven Eurozone countries. We also find that the importance of domestic causes in national uncertainty has increased during the crisis at the expense of imported factors. Dynamic net spillovers reveal that core Eurozone countries are uncertainty exporters before the crisis, while periphery countries transmit uncertainty to other countries during the crisis. An examination of the country which suffered the most during the crisis, using impulse response analysis, reveals that the Greek macroeconomic indicators (stock market, GDP, unemployment, and the Economic Sentiment Index) were affected more by domestic, rather than European uncertainty. The highest responses are indicated during the crisis. Overall, there is positive interdependence between Greek and European uncertainty, which diminishes during the crisis.